Engineering geological zoning of the Scorillo Dam site, Romania - Marunteanu, Cristian; Durdun, Ion (Journal of Nepal Geological Society, 2000)
A model of engineering geological classification and zoning of the Scorillo Dam site in Romania is proposed to optimise the design of the dam and of the grout curtain. The rock mass was classified into four categories: from 1 (good) to 4 (very poor), according to the rock mass quality (RMQ) at the dam site. Parameters available and used to determine the RMQ were lithology, degree of weathering and fragmentation, rock quality designation (RQD), and modulus of elasticity (E). Based on the study, a new design of the dam, its slopes, and the grout curtain was carried out.